PEMBUATAN SIGNAL CONDITIONING UNTUK SENSOR LVDT (LINEAR VARIABLE DIFFERENTIAL TRANSFORMER) - Masria Pane (Saintia Fisika, 2013)
LVDT (Linear Variable Differential Transformer) is one type of displacement sensors. Oscillator and demodulator circuits are designed using the Op Amp. The LVDT sensors work on the principle of magnetic flux in the iron core generated by induction from the primary coil. LVDT input voltage is an alternating voltage (AC), so that the output voltage is also generated in the form of alternating voltage. AC magnitude is obtained by shifting the sensor core by using a micrometer screw. The shift can be seen in the waves generated by analyzing the osciloskop. The resulting waveform changes showed a shift towards the core position of the secondary coil and two secondary one. Position of the input signal that is triggered by a sine wave oscillator circuit which is then transmitted to a primary LVDT input voltage to the sensor LVDT and the voltage of the secondary must be demodulated to produce a DC voltage.Keyword: Signal conditioning, LVDT, Displacement